From Neoliberalism to Neodevelopmentalism: Indonesian’s Investment Policy on the Foreign Capital Post-new Order - Iksan, Muhamad (JASSP, 2022)
This paper aims to describe two problems of investment policy during the New Order regime which leaned towards neoliberal elements or the Washington Consensus; However, after the New Order regime, it was more inclined to a neo-developmental strategy, and saw development strategies related to investment policies change due to internal factors including the presidential election, executive-legislative relations and competing technocrats visvis nationalist economists and external factors such as the global commodity boom. of China’s high demand. The argument of this article is deliberately trying to provide new understanding and insight on investment policies under the administration of President Joko Widodo.